Evaluation of plasma C-reactive protein levels in pregnant women with and without periodontal disease: A comparative study - Sharma Anupriya; Ramesh Amitha; Thomas Biju (Wolters Kluwer Medknow Publications, 2009)
Background and Objectives: Circulating C-reactive protein (CRP) levels are a marker of systemic inflammation and are associated with periodontal disease, a chronic bacterial infection associated with elevation of proinflammatory cytokines and prostaglandins. CRP has been associated with adverse pregnancy outcomes, including preterm delivery, preeclampsia, and intrauterine growth restriction. Furthermore, periodontal disease has been associated with increased risk of preterm low birth weight, low birth weight, and preterm birth. The present study was conducted to assess plasma CRP levels in pregnant women with and without periodontal disease; to evaluate the effect of periodontal therapy on the incidence of preterm delivery; and to compare the incidence of preterm delivery in pregnant women with and without periodontal disease. Materials and Methods: A total of 90 pregnant women aged between 18-35 years with gestational age between 12-28 weeks were recruited and divided into three equal groups (control group, study group, treatment group) of 30 each. Blood samples were taken for estimation of C-reactive protein levels from all groups at 12-20 weeks of gestation, determined using ultrasensitive turbidimetric immunoassay (QUANTIA-CRP US). The treatment group comprised plaque control, scaling, and root planning and daily rinsing with 0.2% chlorhexidine mouth before 28 weeks of gestation. Results: The mean value of C-reactive protein levels in subjects with periodontal disease was higher compared to control group i.e., 1.20 ± 0.247 mg/dl and 1.22 ± 0.250 mg/dl, respectively, compared to 0.713 ± 0.139 mg/ dl ( P = 0.001). The mean value of CRP levels before treatment was greater than the mean value after treatment i.e., 1.22 ± 0.25 compared to 0.84 ± 0.189 ( P < 0.001). The incidence of preterm delivery (< 37 weeks) was 31.7% in the periodontal disease group (study group) compared to 8.3% in the control group ( P = 0.001). The incidence of preterm delivery in the treatment group was 15.0% compared to 31.7% in the nontreatment group (study group). Conclusion: The findings from the study suggest that periodontal disease in pregnant women is associated with increased C- reactive protein levels in early pregnancy, incidence of preterm delivery is higher in pregnant women with periodontal disease compared to healthy controls, periodontal therapy during pregnancy reduces plasma CRP levels and there is decrease in incidence of preterm delivery after periodontal therapy.